PENGARUH PENGALAMAN KERJA INDEPENDENSI, OBJEKTIVITAS, INTEGRITAS, KOMPETENSI TERHADAP KUALITAS AUDIT - Siswo Nurwidodo, 09.05.52.0198; Wahyudi, Djoko (Students Journal of Accounting and Banking, 2012)
Each public accounting firm wants to have an auditor who can work well in an audit. One of which is the work of auditors is to audit the purpose of seeking information about what actions are implemented in an entity that examined order to support the professionalism, the auditor in performing the audit should be guided by the auditing standards set by the Indonesian Institute of Accountants (IAI), which general standards, standards of field work and reporting standards formulation of research problems as follows: The auditor work experience have a positive and significant impact on audit quality. The auditor independence has positive and significant impact on audit quality. The auditor objectivity has positive and significant impact on audit quality. The integrity of the auditors have a positive and significant impact on audit quality.This study aims to determine the effect of work experience, independence, objectivity, integrity, competence has a positive and significant impact on audit quality. The population in this study were all auditors working in public accounting firm in the city of Semarang. The selection of the population in the city of Semarang The population in this study were 266 people, consisting of partners, managers, senior auditors and junior auditors. The number of 266 people found a way to ask the people working in 18 public accounting firm that is in Semarang In this study, the authors use a quantitative analysis which is a form of analysis which is applied to large data can be grouped into a tangible figure kategorikategiri angka.Sedangkan analysis tool in this study using multiple linear regression equation. The research proves that there is the influence of variables on the quality of audit work experience, based on the results of the first hypothesis is accepted. There is the influence of independent variables on the quality audit, based on the results of the second hypothesis can be accepted There is the influence of variables on the quality of audit objectives, based on the results of the third hypothesis is accepted There are influence between variable integrity of the quality audit, based on the results of the fourth hypothesis is accepted There are influence between variablecompetence of quality audit, based on the results of the fifth hypothesis receivedKeywords: work experience, independence, objectivity integrity,competence, quality audit